Industrial production of Phaeodactylum tricornutum for CO2 mitigation: biomass productivity and photosynthetic efficiency using photobioreactors of different volumes - Quelhas, Pedro M. (2020)
The photosynthetic efficiency (PE) and potential of Phaeodactylum tricornutum for CO2 mitigation in industrial tubular photobioreactors (PBRs) of different volumes were evaluated. A preliminary assay was performed at lab-scale to optimize the salt concentration of the culture medium. Interestingly, salinity did not affect the growth of P. tricornutum at concentrations of 2.5, 5, 10, and 20 g L-1. Higher volumetric productivities were achieved in the 2.5-m(3) tubular PBR (0.235 g L-1 day(-1)), followed by 35- and 10-m(3) PBRs. Maximum areal productivities corresponded to 48.5, 45.0, and 12.8 g m(-2) day(-1) for the 35-, 10-, and 2.5-m(3) PBRs, respectively. PE was thus higher in the 35- and 10-m(3) PBRs (2.21 and 2.08%, respectively). The 10- and 35-m(3) PBR showed CO2 mitigation efficiencies of 60 and 41%, respectively, of the CO2 introduced into the PBR, corresponding to 2.3 and 2.5 g of fixed CO2 per g of biomass. Overall, cultivation of P. tricornutum couples high PE and areal productivity when the industrial PBRs were used, particularly PBRs of larger volumes. This improved PE performance with larger PBR volumes strongly suggests that large-scale cultivation of this diatom holds great potential for industrial CO2 mitigation.